Acceleration of Longitudinal Track and Field Performance Declines in Athletes Who Still Compete at the Age of 100 Years - Ganse, Bergita; Braczynski, Anne Kristin; Hoog Antink, Christoph; Knobe, Matthias; Pohlemann, Tim; Degens, Hans (Frontiers in Physiology, 2021)
While physical performance decline rates accelerate after around the age of 70 years, longitudinal athletic performance trends in athletes older than 95 years are unknown. We hypothesized a further accelerated decline in human performance in athletes who still perform at the age of 100 years. To investigate this, longitudinal data of all athletes with results at or over the age of 100 years were collected from the ‘World Master Rankings’ data base spanning 2006 – 2019 (138 results from 42 athletes; 5 women, 37 men; maximum 105 years) and compared to previously published longitudinal data from 80- to 96-year-old athletes from Sweden (1134 results from 374 athletes). Regression statistics were used to compare performance decline rates between disciplines and age groups. On average, the individual decline rate of the centenarian group was 2.53 times as steep (100 m: 8.22x; long jump: 0.82x; shot put: 1.61x; discus throw: 1.04x; javelin throw: 0.98x) as that seen in non-centenarians. The steepest increase in decline was found in the 100-m sprint (t-test: p<0.05, no sign. difference in the other disciplines). The pooled regression statistics of the centenarians are: 100 m: R=0.57, p=0.004; long jump: R=0.90, p<0.001; shot put: R=0.65, p<0.001; discus throw: R=0.73, p<0.001; javelin throw: R=0.68, p<0.001. This first longitudinal dataset of performance decline rates of athletes who still compete at 100 years and older in five athletics disciplines shows that there is no performance plateau after the age of 90, but rather a further acceleration of the performance decline.